Manejo y conservación de suelos en plantación de arroz bajo riego en el Ecuador - Pereira Quisintuña, Carlos Julio (2019)
The present research work, whose results support the writing of this monograph was carried out at the Technical University of Babahoyo, Faculty of Agricultural Sciences, School of Agricultural Engineering, Intensive rice production can lead to increased compaction of the deeper layers of the soil as a result of the use of heavy machinery, in addition to that, the production under irrigation can present problems in the development of the crop. The patterns of use that the rice farmer gives to the soil in rice cultivation is ambiguous, since he has been practicing it for years without having a clear alternative in its initial preparation, the farmer performs the fangueo for the reduction of production cost in the use of herbicides. Rice soils have generally remained in constant exploitation, with monoculture prevailing and a whole "cocktail" agricultural inputs that have been transforming their physical, chemical and biological state for years. The soil managed under the conventional system (monoculture), tends to destroy the structure, causing alterations in chemical, biological and other physical indicators. It is concluded that the conventional soil management system for the production of rice under irrigation in Ecuador alters the quality of the soil, which may affect crop yields. The conventional production system (monoculture), demands the continuous use of inputs to obtain high yields. The soil management systems that are based on maintaining the crop residues on the surface contribute to improve soil health. Management practices that are based on minimum tillage or zero tillage improve soil quality and productivity of rice cultivation. It is recommended to promote the use of practices that are based on maintaining crop residues on the soil surface and reducing tillage to improve their health and increase yields on rice cultivation under irrigation conditions. Conduct research to validate conservation management techniques in rice producing areas under irrigation in the country